CHARACTERISTICS OF CHRONIC RENAL FAILURE PATIENTS IN THE HEMODIALYSIS UNIT OF TANGERANG CITY HOSPITAL - OU, Taty Damayanty; Dewi Purnamawati (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
Chronic kidney failure, a non-communicable disease, is included in the top 10 diseases in Indonesia. This study aims to study the characteristics of chronic renal failure patients in the Hemodialysis Unit at Tangerang City Hospital, Banten. This study uses a quantitative approach to crossectional design. The population was 213 hemodialysis patients, and data were collected using medical record data. The analysis is carried out descriptively. The results of This study showed that more than half of the male sex was 114 people (53.52%), and the remaining 99 people (46.48%) were women. The age varies quite a bit from 15-24 years, as much as 0.94%, to the elderly. The most age in age group of 45-54 years was 31.94%. The most educated from the secondary education category was 112 people (52.58%); in the remaining 101 orgs, only 9.39% were highly educated. And in terms of work, almost half of the respondents were housewives as many as 85 people (39.91%). From this study, it can be concluded that the characteristics of renal failure patients have changed, especially in of age; it was found that 0.94% were young, 15-24 years old. Promotive and preventive efforts are needed to be related to the incidence of kidney failure at a young age by increasing the level of education.